Biological And Biochemical Effects Of Thyme (Thymus Vulgaris L.) Plants Found In The Al-Baha Area Region In Reducing Weight In Obese Rats (International Journal of Environmental Sciences, 2025)
Natural products remain a significant resource for developing effective and innovative therapeutic agents. Objectives: The current research aims to illustrate the biological and biochemical effects of thyme plants from the Al-Baha area in reducing weight in obese mice. Materials and Methods: Thirty white male albino mice of Sprague-Dawley strain, weighing around 150 ± 10 grams, have been utilized in this research. All mice have been fed a standard nutrition for one week prior to the commence of the trial as an adaptation duration. Six mice (control) were fed on the basal diet, while 24 mice have been nourished on a high-calorie regime containing 20% animal overweight to induce obesity for about three weeks. Feeding intervention continued for 28 days, where 2%, 4%, and 6% of thyme plant powder was added. After sacrificing rats, different biological and biochemical changes were recorded. Results: Body weight gain (BWG), serum glucose, and thyroid gland function were increased significantly in obese mice, while feeding on dried powder of 2%, 4%, and 6% thyme decreased BWG greatly. The highest decrease was recorded for 4% of thyme powder.High levels of certain compounds, which are responsible for several diseases, especially cardiovascular disease, may be reduced by thyme, which contains bioactive compounds and positive biochemical effects. Therefore, powders of thyme may be recommended to be added to the ordinary diet.